The strange message in the parchment - Keene, Carolyn (New York : Grosset & Dunlap, 1977)
While trying to recover a set of stolen parchment paintings, Nancy Drew becomes involved in tracking a kidnapper and extortionist.
Stolen! -- Triple Creek Farm -- Plaintive bleating -- Eezy shaw -- Bird attack -- "No speak English!" -- A mean ram -- The mystery boy's story -- Midnight thief -- Running footprints -- A tough suspect -- Telltale glove -- A paint disaster -- Important information -- Secret notes -- Reinforcements -- A denial and a chase -- The first confession -- A strange reunion -- Found money.
750L
Accelerated Reader AR
edited hb 2015-06-16
Keywords: Drew, Nancy -- (Fictitious character) -- Fiction; Drew, Nancy -- (Fictitious character); Mystery and detective stories; Women detectives; Women detectives; Kidnapping; Extortion investigation; Extortion investigation; Adventure and adventurers; Detective and mystery stories; Drew, Nancy (Fictitious character); Women detectives; Kidnapping; Extortion investigation; Adventure stories; Fiction; Fiction